Acupuncture Relieves Stress-Induced Depressive Behavior by Reducing Oxidative Stress and Neuroapoptosis in Rats - Cheng, Wen-Jing; Li, Peng; Huang, Wen-Ya; Huang, Yang; Chen, Wen-Jie; Chen, Yi-Ping; Shen, Jun-Liang; Chen, Jian-Kun; Long, Na-Sha; Meng, Xian-Jun (Frontiers in Behavioral Neuroscience, 2022)
Oxidative stress is closely related to the occurrence of depression. Acupuncture has been proved to be an effective method for treating depression. In order to explore the mechanism of the antidepressant effect of acupuncture, this study performed acupuncture prevention on chronic unpredictable mild stress (CUMS) depression model rats, and observed the effect of acupuncture on hippocampal oxidative stress and Nrf2 signaling pathway. Male SD rats were randomly divided into control group, CUMS group, acupuncture group, and fluoxetine group (n = 10/group). Fluoxetine, a common antidepressant, was used as a positive control drug in this study. In the fluoxetine group, rats were given fluoxetine (2.1 mg/kg) intragastrically once a day for 28 days. The acupoints of Shangxing (GV23) and Fengfu (GV16) were applied in acupuncture group, once every other day for 14 times in total. Behavioral tests and biological detections were used to evaluate the effects of the interventions and the changes of factors related to oxidative stress, Nrf2 pathway, and neuronal apoptosis. The results showed that both acupuncture and fluoxetine could increase sugar preference rate in SPT and decrease immobility time in FST in depression model rats. It also significantly decreased oxidative stress products such as ROS and H2O2, and elevated the protein and mRNA expressions of Nrf2 and HO-1. From Nissl’s staining, there were more abundant nerve cells in two intervention groups compared with CUMS group. Plus, acupuncture down-regulated the expression levels of Bax and caspase-3 and up-regulated the expression of Bcl-2. Our findings indicate that acupuncture improved depression-like behaviors of CUMS rats. And CUMS-induced depression-like behaviors in rats were related to oxidative stress and neuronal apoptosis in hippocampus. Acupuncture showed antidepressant effects in reducing oxidative stress products via regulating the Nrf2/HO-1 signaling pathway so that prevented neuronal apoptosis.